2015
DOI: 10.1039/c5cc00388a
|View full text |Cite
|
Sign up to set email alerts
|

Sonication-assisted alcoholysis of boron nitride nanotubes for their sidewalls chemical peeling

Abstract: Boron nitride (BN)-based nanomaterials attract considerable attention due to their unique properties. In this study, we found that sonication treatment of multiwalled boron nitride nanotubes (BNNTs) in primary alcohols had led to chemical peeling of their sidewalls through alcoholysis, thereby producing boron nitride nanoribbons (BNNRs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 38 publications
1
40
1
Order By: Relevance
“…These thermal, elemental, and spectroscopy analyses results together provide strong evidence that the exfoliated BNNSs are covalently grafted with sucrose moieties and hydroxyl and amine groups (‐OH and ‐NH x ). It is likely that during the mechanochemical exfoliation, sucrose molecules react with active edges or surface defects in the fractured BNNSs, forming boronate ester, amine, and other possible functional groups, similar to the alcoholysis of BN nanotubes in liquid alcohols by ulrasonication reported earlier …”
mentioning
confidence: 59%
“…These thermal, elemental, and spectroscopy analyses results together provide strong evidence that the exfoliated BNNSs are covalently grafted with sucrose moieties and hydroxyl and amine groups (‐OH and ‐NH x ). It is likely that during the mechanochemical exfoliation, sucrose molecules react with active edges or surface defects in the fractured BNNSs, forming boronate ester, amine, and other possible functional groups, similar to the alcoholysis of BN nanotubes in liquid alcohols by ulrasonication reported earlier …”
mentioning
confidence: 59%
“…With the assistance of sonication, the walls of highly-crystalline BNNTs were found to be peeled off and formed BN nanoribbons (BNNRs) in various primary alcohols solvents. 80 IR tracking revealed the formation of B-O, B-O-C and O-B-O vibration modes in a product, which were not originally present in the BNNTs. These alcoholysized compounds with their edges terminated by -OR groups can be well dispersed in alcohol solvents.…”
Section: Hydroxyl (-Oh) and Alkoxy (-Or) Groupsmentioning
confidence: 97%
“…1 . Our previous work reported unzipping of BNNTs into BNNRs in alcohol under sonication which indicated that alcohol molecules activated BN bonds through coordination for subsequent hydrolysis [ 17 ]. Furthermore Liao et al [ 19 ] showed that chemical sharpening, shortening, and unzipping of BNNTs occurred in water-ammonia mixture because ammonia molecules coordinated to the B atoms as Lewis base, followed by hydrolysis of BN bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers including our group have studied simple ways of producing BNNRs without using pre-production step, special treatment, and equipment. Our group discovered that longitudinally unzipped BNNTs can be produced via alcoholysis using alcohol with long alkyl chains under sonication because the chemical interaction between boron atom of BNNTs and oxygen atoms of alcohol lead to generation of alkyl chain-connected BNNRs [ 17 ]. However, alkyl chains attached on BNNR edges largely deteriorate their chemical reactivity.…”
Section: Introductionmentioning
confidence: 99%